COVID-19 Knowledge, Awareness and Perceived Stress among Jordanian Healthcare Providers - Aborajooh, Emad; Mafrachi, Baraa; Yassin, Muhammad; Alhalaseh, Lana; Dwairi, Rami; Abu- Yaghi, Nakhleh; AL-Khazraji, Yahya; Abufaraj, Mohammad (Jordan Medical Journal, 2023)
Background: Healthcare providers (HCPs) are frontline workers during the COVID-19 pandemic. They are prone to increased risk of infection and psychological stress. Aims: To measure levels of knowledge, awareness, and stress about COVID-19 among HCPs. Methods: This cross-sectional study of 397 HCPs utilized an internet-based validated questionnaire to evaluate knowledge about COVID-19, the availability of personal protective equipment (PPE), future perceptions, and psychological distress. Univariate and multivariate ordinal logistic regression analyses were used to evaluate factors associated with the degree of knowledge and psychological stress. Results: Overall, 24.4% showed excellent knowledge, while 54.4% and 21.2% demonstrated good and poor knowledge, respectively. Social media (61.7%) and medical papers (57.7%) were the most commonly used sources of information. Being a female (β=0.521, 95% CI 0.049–0.992), a physician (β=1.421, 95% CI 0.849–1.992), or using published literature to gain knowledge (β=1.161, 95% CI 0.657–1.664) were positive predictors of higher knowledge levels, whereas having higher levels of stress (β= -0.854, 95% CI -1.488 to -0.221) and using social media (β= -0.434, 95% CI -0.865 to -0.003) to gain information were negative predictors of knowledge levels. The availability of PPE was significantly associated with lower psychological stress (p=.01). Conclusion: Institutions have to provide free evidence-based resources for HCPs about COVID-19, and PPE should be secured to reduce the amount of psychological stress associated with treating COVID-19 patients, as well as to improve their knowledge and the subsequent care provided